DNA a mikroRNA cipové technologie v diagnostice a predikci u pacientů s renálním karcinomem - Slabý, O; Svoboda, M; Michálek, J; Vyzula, R (Klinicka onkologie, 2009)
Renal cell carcinoma accounts for approximately 3% of adult cancers and has the highest lethality of urological malignancies. Research focusing on carcinogenesis and development of renal cell carcinoma has led to the identification of the key signalling pathways and consequently targeted cancer therapy which improves time to progression or overall survival of renal cell carcinoma patients. Today, microarray technologies are some of the most efficient methods used in gene expression studies. Through one microarray experiment we can simultaneously determine the expression of thousands of genes, thus facilitating research of examined biological models. The most frequently used of the microarray technologies are DNA microarrays enabling global analysis of the mRNA (messenger RNA) expression, while recently, microarray platforms modified to detect short non-coding RNAs (microRNAs) have been employed (microRNA microarrays). MicroRNAs significantly affect the behaviour of tumour cells by post-transcriptional regulation of the gene expression. In the research into renal cell carcinoma, microarray technologies have been applied in more than twenty studies over the past five years. These papers describe the potential of microarrays to distinguish tumour tissue from normal renal parenchyma, to classify renal cell carcinomas according to histological subtypes, to identify expression profiles predicting metastasizing in primary renal tumours, and to determine the prognosis of particular renal cell carcinoma patients. The aim of this review is to summarize the results from microarray studies of renal cell carcinoma realized to date and to present their potential usage in diagnostic and therapeutic protocols.
Keywords: nádory ledvin; sekvenční analýza hybridizací s uspořádaným souborem oligonukleotidů; karcinom z renálních buněk; Carcinoma, Renal Cell; mikro RNA; Oligonucleotide Array Sequence Analysis; Gene Expression Profiling; Humans; lidé; Kidney Neoplasms; Prognosis; prognóza; stanovení celkové genové exprese; MicroRNAs